Classificação e busca ativa de pacientes com imunodeficiência primária atendidos em um Hospital Terciário do Oeste Paulista - PEREIRA, Denise Helena Boton (2019)
Objective: Classification of Primary Immunodeficiencies (PIDs) of patients followed at the Immunodeficiency/ Infectious Diseases outpatient Clinic; the active search for patients candidates to PIDs hospitalized in the pediatrics, infectious diseases yards and in the pediatric intensive care unit (ICU) at the Regional Hospital of Presidente Prudente (HR). Method: Between September/2017-September/2018, weekly visits were conducted in search for patients who had been showing alarming signs for PIDs. The medical records analysis was performed in outpatients attended between January/2014-August/2018. Results: In the active search, 28 patients were evaluated with a higher number of children and adolescents compared to adults. In the outpatients clinic 97 patients filled the inclusion criteria. Seventy- two (74.2%) had multiple hospital admissions due to recurrent infections. Among the most prevalent diagnoses are low or no vaccine response and/or to polysaccharide antigens, Variable Common Immunodeficiency and selective IgA deficiency. Conclusion: The results highlight the importance of the installation, maintenance and optimization of this service. The greatest benefit is the improved quality of life for these patients and families with lower public health expenditure